Diet as an element of pro-health style of life in the conditions of toxic environmental hazards - Pasek, Marcin; Wilk, Barbara (Journal of Education, Health and Sport, 2017)
In the times of progressing expansion of civilization diseases, more precise methods of fight against them are planned. In many cases this confrontation takes place only when effects occur. Thus deepening knowledge on the reasons of diseases and proper prevention, does not lose its validity. Procedures preceding as well as following occurrence of disease symptoms, refers to healthy life style with its inseparable elements: avoidance of stresses, physical activity, contact with natural environment, reasonably long sleep and balanced nutrition. The aim of this study is to assess the meaning of the selected food ingredients in detoxification of organism at the ecologically endangered areas. Diet is treated as a protection against environmental stressors, and apart from development of health awareness, it will also result by improvement of quality of life. Methods of fight of human organism against the symptoms of poisoning of the organism with specification of enzymatic and not enzymatic antioxidant mechanisms are discussed in the study. This analysis is supplemented by propositions of practical dealing with these threats by respecting rules of detoxification diet.